Pengaruh Perceived Usefulness, Perceived Ease of Use, dan E-Security terhadap Reuse Intention pada Pengguna E-Wallet DANA di Daerah Istimewa Yogyakarta - Afifah, Inti Nurul Nur; Indarto, Muhammad Roni (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
Several e-wallet companies compete with each other to maintain the existence of using their services, one of which is the DANA e-wallet. The aim of this research is to determine the influence of perceived usefulness, perceived ease of use, and e-security on reuse intention among DANA e-wallet users in the Special Region of Yogyakarta. This research uses independent variables; perceived usefulness, perceived ease of use, and e-security while the dependent variable is reuse intention. The population in this study were DANA e-wallet users in the Special Region of Yogyakarta. The sampling technique with non-probability sampling uses purposive sampling technique. The sample used in this research was 100 respondents. Data collection techniques were carried out using Google forms. This research uses multiple regression analysis with the SPSS version 26 macro analysis tool. This research found that perceived usefulness (X1), perceived ease of use (X2), and e-security (X3) had a positive effect on reuse intention among DANA e-wallet users in the Special Region of Yogyakarta.